Good News — Bad News: Combined Ocean Change Drivers Decrease Survival but Have No Negative Impact on Nutritional Value and Organoleptic Quality of the Northern Shrimp - Chemel, Mathilde; Noisette, Fanny; Chabot, Denis; Guscelli, Ella; Leclerc, Luc; Calosi, Piero (Frontiers in Marine Science, 2020)
Nutritional and organoleptic qualities (taste, smell, texture, appearance, ) are key characteristics of seafood when it comes to defining consumer choices. These qualities, which are determined by the biochemical properties of the seafood, can be altered by environmental conditions such as those imposed by ongoing global ocean change. However, these effects have rarely been studied despite their potential important economic and dietary implications; many human communities depend upon seafood as a primary source of nutrition and/or income from the associated seafood industry. The Northern shrimp, Pandalus borealis, makes the 3rd most valuable fishery in Eastern Canada, and figures among the most important fisheries in the North-Eastern Atlantic. This study aimed to determine the impact of combined ocean warming, acidification and hypoxia on a) muscle mineral content as proxy for nutritional quality, and b) the taste, smell, texture, and appearance as proxies for organoleptic quality of this commercially important species. These proxies were determined after an exposure of 30 days under laboratory conditions to different ocean global change scenarios of temperature (2, 6 and 10 °C), pH (7.75 and 7.4) and oxygen (100 and 35% relative to air saturation), in isolation and in combination. Shrimp survival decreased by 25% in the scenario combining the elevated temperature and low pH, and by an additional 31% when hypoxia was superimposed. Mineral contents were globally higher in shrimp exposed to the highest temperature, while organoleptic attributes were comparable across all scenarios tested. Thus, while we do not expect nutritional value and organoleptic quality of shrimp, broadly speaking, to be altered by global changes even in areas where conditions will correspond to our warmest (10 °C) and lowest pH (7.4) scenarios, the lower survival rate we report could negatively impact the viability of shrimp populations and consequently the shrimp industry. This may be particularly true for areas that are currently becoming or are expected to become hypoxic.